The Relationship between Coping Mechanisms and the Level of Stress in Type 2 Diabetes Mellitus Patients - Zuriati, Zuriati; Azizah, Rahmalia Nurul; Suriya, Melti; Zahlimar, Zahlimar (Karsa Husada Health Institute Garut, 2024)
Diabetes Mellitus is a chronic disease that has a negative impact on the physical and psychological effects of sufferers, the psychological impact that occurs is like stress, Stress is twice as easy to attack diabetics, one way to adapt to stress in diabetics is with coping mechanisms. This research is to determine the relationship between coping mechanisms and the stress level of type 2 diabetes mellitus patients in Ambarawa Pringsewu. This type of research is quantitative research with a cross-sectional correlation approach design. The population of this study was 324 patients with type 2 diabetes mellitus at the Ambarawa Pringsewu Community Health Center, with a sample of 76 people taken using the Accidental Sampling technique. The research instrument used a questionnaire, and data analysis was carried out univariately and bivariately using the chi square test. The results of the analysis obtained were that the majority of respondents with maladaptive coping mechanisms were 72 (94.7%), with the category of severe stress level being 41 (53.9%). Analysis results using the chi square test obtained a result of 0.000. This means that there is a relationship between coping mechanisms and the stress level of type 2 diabetes mellitus patients at the Ambarawa Pringsewu Community Health Center. Suggestions are expected for people with type 2 diabetes mellitus to always increase their knowledge of each disease they suffer from, in order to be able to maintain the desired health and it is hoped that people with type 2 diabetes mellitus will be more diligent in checking their blood sugar every month at the nearest health service to improve their quality of life long.